Development of a mass spectrometry-based metabolomics workflow for traceability of wild and cultivated Cordyceps sinensis. Issue 11 (2nd November 2022) - Ding, Bo; Li, Hanxiang; Huang, Hongbo; Xie, Jianjun; Wang, Zhiyuan; Chen, Wenrui; Tao, Yiwen
Abstract: Cordyceps sinensis, as an expensive traditional Chinese medicine and edible fungus mycelium, lacks an effective quality evaluation method, especially and cultivated Cordyceps sinensis . In this study, a feasible workflow method was developed for traceability evaluation of wild and cultivated Cordyceps sinensis, based on mass spectrometry-based metabolomics. Mass spectrometry data were firstly acquired from Cordyceps sinensis, samples by liquid chromatography-quadrupole and time of flight mass spectrometry. Characteristic mass spectrometry peaks were extracted by applying the MZmine. Then significant markers were obtained from Cordyceps sinensis samples by orthogonal partial least square discriminant analysis. Then, identification of significant markers were identified by MS-FINDER data analytics. The results showed that Changdu, the other four wild origins (Naqu, Xinghai, Yushu and Guoluo) and cultivated samples could be significantly distinguished. This identified significant markers of Cordyceps sinensis, including 174 special significant markers for the wild samples, 204 special significant markers for the cultivated samples and 87 share significant markers. Number of 87 shared significant markers were identified in the wild and cultivated Cordyceps sinensis, especially 28 confident significant compounds, such as adenosine, riboflavin, tyrosine, arginine and glutamine. These shared significant markers might support the quality control of multi-targets of Cordyceps sinensis, compared with a single target in the Chinese Pharmacopoeia. The special significant markers indicated that cultivated Cordyceps sinensis was different from the wild based on mass spectrometry-based metabolomics. In the comparison of chromatographic fingerprint technology, it was found that the established feasible workflow method was easy to acquire significant markers and traceability of Cordyceps sinensis . This feasible workflow method has great potential to be successful for comprehensive and traceability evaluation of the wild and cultivated Cordyceps sinensis.